Identidades brasileiras: histórias de vida e relações étnico-raciais no Ministério Público Federal do Brasil - Portela, Caio Barbosa (2022)
This research consists of an anthropological study that starts from the following reflection: how each life story combined with the knowledge we acquire from critical racial theories can affect the perception we have about our own identity and that of the Other, interfering in self-declarations and hetero-identifications, central instruments in the implementation of the racial quota policy in Brazil? The investigation is based on data collected at the Brazilian Federal Public Ministry (MPF). A situational analysis of the empirical field and a bibliographic review on the concepts of race, miscegenation and ethnic-racial identity were carried out. The methodologies used were: Self-reflection and Life Stories (HV). The research techniques adopted were observant participation, archival ethnography and ethnographic interview. Six interviews were carried out with self-declared people: white (2), yellow (1), black (2) and brown (1 who declared herself to be Améfrican), active in the affirmative policies of the MPF. The theoretical-methodological foundations of this investigation are based on the works of Nogueira ([1955] 2006), Fernandes ([1972] 2013), Hampâté Bâ (1981), Ramose (1999; 2002; 2021), Favret-Saada (2005) , Queiroz (1988), Paulilo (1999), Meksenas (2002), Munanga ([2004] 2019), Beaud & Weber (2007), Domingos (2017; 2020) and Balduíno (2021).